Connector sets and interconnect components to be used in optical fibre communication systems. Product specifications. Type LF3 APC simplex terminated on IEC 60793-2-50 category B1.1 and B1.3 singlemode fibre with titanium composite ferrule for category C Part 16-1, (31st October 2013) - British Standards Institution,
No abstract available